Oral Health Literacy Of First Year University Students - Jaafar, Azlan; Rosli, Rafiuddin; Shamsulhuda, Nursyazwani; Samsudin, Ahmad Dzulfikar; Mumin, Nazirah Ab (IIUM Medical Journal Malaysia, 2017)
Introduction: Oral health literacy (OHL) can be different between science stream and non-science stream students as the exposure to knowledge of science is low among non-science stream. This situation can lead to unhealthy oral health behaviour and later increase the oral health problem among the non-science stream group. Thus, the study conducted aimed to compare the oral health literacy among science stream and non-science stream students and other factors associated, among first year students of Universiti Sains Islam Malaysia (USIM). Materials and Methods: A crosssectional study was conducted among 256 students from various faculties of USIM consisted of both science and non-science stream group. A validated Malay version, self-administered questionnaire of Oral Health Literacy Instrument (OHLI) was used to assess their OHL. Data gathered was later analysed using IBM SPSS version 21.0. Multiple logistics regression was used to determine the associated risk factors of OHL. Results: Study indicated that science stream students compared to non-science stream students have higher oral health literacy (OR= 6.98; 95% CI= 3.64, 13.39; p< 0.001). Besides, students whom their mother’s education level are high have higher OHL compared to their counterparts (OR= 2.31; 95%CI= 1.24, 4.28; p= 0.008). Conclusion(s): An exposure to indepth knowledge of science has an effect on OHL. Science stream students have high oral health literacy compared to non-science group. This finding give some ideas on suitable methods of oral health promotion that can be implemented among science and non-science stream background of students especially in school.